"My second choice was Armenia": motivations for diasporic return migration among Iranian Armenians to Armenia. Issue 16 (10th December 2022) - Fittante, Daniel; Barry, James
ABSTRACT: This article examines the concept of ethnic return migration in the permanent settlement of Iranian Armenians in the Republic of Armenia. Scholarship on ethnic return migration (or diasporic "homecoming") almost exclusively focuses on mobility to or from affluent Western multicultural democracies in North America, Europe and Oceania. This article therefore provides a new opportunity to test the generalizability of existing models on return migration. Iranian Armenians fit within what the scholarship refers to as ethnic or diasporic return migrant – that is, migrations motivated, largely, by affective orientation to ethnicity and perceived home country. However, these migrations are not primarily motivated by ethnic or national longing for an ancestral homeland, but rather a variety of economic and political reasons sit behind these migrants' decisions to choose Armenia instead of moving to a Western country or remaining in Iran.